2011
DOI: 10.1002/ccd.22675
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde transcatheter closure of ventricular septal defects in children using the Amplatzer Duct Occluder II

Abstract: Transcatheter retrograde device closure of selected cases of Ventricular Septal Defects using the Amplatzer Duct Occluder II is simple and appears safe in the short term and can be completed within a short fluoroscopic time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
3
26
1
3
Order By: Relevance
“…While the small diameter of the arterial vessels in infants poses an obstacle for the selection of the retrograde approach, changes in the profile of the delivery systems allowed the use of transarterial implantation technique in older children and adolescents. Recently, with this technique the Amplatzer muscular occluder device (10, 11) and ADO II device (12) have been implanted successfully in adolescents and children with congenital VSD. There are also scant case reports in that retrograde technique was used (1315).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the small diameter of the arterial vessels in infants poses an obstacle for the selection of the retrograde approach, changes in the profile of the delivery systems allowed the use of transarterial implantation technique in older children and adolescents. Recently, with this technique the Amplatzer muscular occluder device (10, 11) and ADO II device (12) have been implanted successfully in adolescents and children with congenital VSD. There are also scant case reports in that retrograde technique was used (1315).…”
Section: Discussionmentioning
confidence: 99%
“…However, Hijazi et al (7) and Koneti et al (12) reported that kinking resistance could also occur during the retrograde approach and keeping 0.018 inches wire within the catheter until the closure device is pushed to the tip of the delivery catheter would overcome this problem. Jameel et al (10) reported difficulty to cannulate the defect and prolonged procedure time due to repeated kinking of the delivery sheath in a patient with apically located muscular defect (fluoroscopy time was 74.3 min, and procedure time was 95 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldstein and his associates [240] utilized clamshell occluder to close the VSDs. Perioperative closure of muscular VSDs was used in complex congenital heart defects as a part of overall management of the patients [241] Subsequently, buttoned device [242,243], Amplatzer muscular VSD device [244,245], detachable steel coil [246], Gianturco coils [247], Amplatzer membranous VSD occluder [248], wireless devices (Detachable balloon & transcatheter patch) [249], CardioSEAL/ STARFlex devices [250], Nit-Occlud (Nickel-Titanium Spiral Coil) [251], Amplatzer Duct Occluder [252] and Amplatzer Duct Occluder II [253] devices were used for transcatheter occlusion of VSDs.…”
Section: Ventricular Septal Defectmentioning
confidence: 99%
“…The advantages of ADO II are its smaller delivery sheath, soft shape, and flexible implantation approach (arterial or venous side). [3]…”
mentioning
confidence: 99%